Factors Associated with Perceived Feasibility and Willingness of Non-Psychiatric Doctors in Japan to Treat Depressed Patients. (August 2013) - Inagaki, Masatoshi; Ohtsuki, Tsuyuka; Ishikura, Fuminobu; Kodaka, Manami; Watanabe, Yoichiro; Yamada, Mitsuhiko
Objectives: We previously reported that many non-psychiatric doctors in Japan believe that treating depression was not part of their duties. Educational interventions must address motivation of physicians to play a role in depression care. In this study, we explored factors associated with perceived feasibility and willingness of non-psychiatric doctors in Japan to treat depression. Methods: The study population included non-psychiatric doctors of the General Physician-Psychiatrist (G-P)Network group in Japan. We explored perceived feasibility and willingness to treat depressed patients, and examined preliminary associations with attitudes toward depression (the Depression Attitude Questionnaire: DAQ) and current depression treatment in routine medical practice. Results: Responses were obtained from 56 non-psychiatric doctors (response rate: 35.4%). The doctors who scored high on the "Professional" and "Pessimism" subscale of the DAQ believed that treating depressed patients was not feasible (χ 2 = 13.6, p < 0.01; χ 2 = 7.3, p < 0.05, respectively) and were not willing to treat depressed patients (χ 2 =9.4, p < 0.01; χ 2 = 6.6, p < 0.05, respectively) as part of their routine medical practice. The doctors who scored high on the "Professional" subscale referred fewer depressed patients to psychiatrists ( r = −0.33, p < 0.05), and those who scored high on the "Pessimism" subscale recognized fewer depressed patients ( r = −0.39, p < 0.01). Conclusions: The present study showed that attitudes toward depression were associated with perceived feasibility and willingness to treat depressed patients and with under-diagnosis of depression. Educational interventions optimized for these attitudes should be developed to improve recognition and treatment of depression in Japan.